KATA-KATA VULGAR DALAM MEME CALON PRESIDEN FIKTIF NURHADI ALDO - Afif Julianto Iriana; Sariah Sariah Sariah (Kantor Bahasa Provinsi Gorontalo, 2020)
Freedom of speech is the right of everyone. Does this study aim to reveal such as (1) what vulgar words are used in Nurhadi-Aldo's memes ?; (2) how many vulgar words were used ?; (3) where do the vulgar words come from; and (4) what kind of word class of vulgar words are used? The approach used in this research is descriptive. The research begins by collecting data from data sources that are indicated to contain vulgar elements in it. After the data is determined, the researcher analyzes it with a semantic approach to determine the meaning and then how often the word is used, the origin of the word, the intent to be conveyed, and its relation to culture. This study shows this clearly by finding 28 vulgar words that are used 55 times in 37 memes. The vulgar things in this Nurhadi-Aldo meme are dominated by sexual matters and are not limited to Indonesian.